Chemical Synthesis of Mono‐ and Bis‐Labeled Pre‐MicroRNAs1. Issue 46 (23rd September 2013) - Pradère, Ugo; Brunschweiger, Andreas; Gebert, Luca F. R.; Lucic, Matije; Roos, Martina; Hall, Jonathan
<x xml:space="preserve">Abstract</x> A chemical method for the post‐synthetic labeling of pre‐miRNAs on solid support using easily accessible reagents was developed. The procedure was employed to generate a library of 31 pre‐microRNAs carrying labels commonly used in chemical biology, including Cy3, trioxalen, biotin, and BHQ‐1.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>